The effect of environmental factors on spatial-temporal variation of heterobranch sea slug community in northern Taiwan - Chan, Ho Yeung; Chang, Yen-Wei; Chen, Li-Shu; Nishida, Kazuki; Shao, Yi Ta (Frontiers in Marine Science, 2022)
Sea slug (Subclass Heterobranchia) biodiversity is an important element of marine coral reef communities. However, due to their small size and cryptic behavior, few studies have examined their spatiotemporal variation. Taiwan is in the middle of East Asia Island Arcs, where it is one of the hotspots of sea slug diversity. Meanwhile, the northeast coast of this island lies within the subtropical monsoon region, where the climate shifts from a warm southwest monsoon (SW: May to Sep) to a cold northeast monsoon (NE: Oct to Apr). Between the monsoons, distinct temperatures and currents result in different community structures. To understand how those environmental factors (i.e., monsoon season, diel period and water depth) influence sea slug species richness and assemblages, we surveyed these invertebrates monthly at both night and day by diving in a marine protection area (CJ) and at a nearby non-protected site (MR) from May 2020 to Apr 2021. We showed that the species composition in our sampling area was highly consistent with what was found in Okinawa and Pescadores island, but less similar to those in southern Taiwan or Hong Kong. On the northeast coast of Taiwan, sea slug number and abundance were both higher in CJ than MR, but biodiversity (H’) and the species evenness index J’ was lower in CJ than MR. Additionally, cluster analysis indicated that the sea slug assemblages differed between the two sites. Monsoon season significantly influenced both species richness and species assemblages, with species richness during SW being significantly higher than in the NE monsoon and species assemblages also being distinct between these two seasons. Moreover, species richness increased with water depth (within the surveyed range of 0-25 m). Diel period did not exert a strong impact on sea slug biodiversity, except for species richness at CJ, where it was higher during the day than at night. Our study suggested that changing currents between the monsoon seasons could transport individuals originating from either the north or south of these island arcs. Furthermore, temperature and food sources may differ between seasons and depths, thereby influencing sea slug assemblages in this region.